EVALUATION OF THE USE OF FAAS FOR SR/CA CONCENTRATION ANALYSIS OF PORITES FROM AMBON BAY AND JUKUNG ISLAND CORAL - Idha Yulia Ikhsani; Eki Naidania Dida; Sri Yudawati Cahyarini (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2017)
The ratio of Sr/Ca concentration in coral is usually used as paleothermometer. Inductively Coupled Plasma (ICP) is an instrument, which is often used to analyze Sr/Ca concentration in Porites sp. The method is very sensitive and requires small amount of sample. However, the availability of this instrument is very limited. To deal with it, Flame Atomic Adsorption Spectrophotometer (FAAS) is an alternative in order to analyze the concentration of various elements include Sr and Ca. The aim of this study was to evaluate the result of the analysis methods of strontium and calcium concentration in coral using FAAS and compared to ICP results. Sample of Porites coral was taken from Ambon Bay and Jukung Island. The strontium and calcium concentration were analyzed using Flame Atomic Adsorption Spectrophotometer (FAAS). The results showed that the average of ratio Sr/Ca in coral from Ambon Bay and Jukung Island were 8.71 and 7.708 mmol/mol. The monthly variation of ratio Sr/Ca in coral from Ambon Bay were 6.28 - 10.24 mmol/mol, while in coral from Jukung Island were 1.005 - 10.914 mmol/mol. Result of FAAS analysis was too broad in range compared to ICP, ie 8.462 - 8.807 dan 8.45 – 8.7 mmol/mol. The range was estimated due to the occurrence of strontium and calcium ionization reaction in flame of FAAS. Keywords: FAAS, coral, ratio Sr/Ca